In Vitro Activities of Ceftaroline/Avibactam, Ceftazidime/Avibactam, and Other Comparators Against Pathogens From Various Complicated Infections in China. (13th November 2018) - Zhou, Menglan; Cheng, Jingwei; Liu, Yali; Hu, Yunjian; Liu, Yingmei; Lu, Juan; Zhang, Shufang; Yu, Yunsong; Huang, Xun; Yang, Qing; Liao, Kang; Jin, Yan; et al.
Abstract: Background: We conducted a national antimicrobial surveillance study of both gram-positive and gram-negative organisms isolated from hospitalized patients. This report presents data on antimicrobial susceptibility among 4998 organisms collected in China between 2012 and 2014. Method: The minimum inhibitory concentrations (MICs) and susceptibilities of ceftaroline/avibactam (CPA), ceftazidime/avibactam (CZA) and a range of comparative agents were determined according to guidelines established by the Clinical and Laboratory Standards Institute (CLSI). Results: The highest overall susceptibility levels for all Enterobacteriaceae during the study period were observed for CPA, CZA, doripenem (DOR), meropenem (MEM), and amikacin (AMK), which were all >90%. However, both CPT and CAZ alone and in combination with avibactam showed low activities for Acinetobacter spp., whereas CPA and CZA exhibited MIC90 values for Pseudomonas aeruginosa that were reduced by 4- and 8-fold, respectively, compared with those of CPT and CAZ. High susceptibilities of Acinetobacter spp. and P. aeruginosa to colistin and P. aeruginosa to AMK were observed. For the gram-positive strains, no significant activity changes were seen for Enterococcus, Staphylococcu s, and viridans group streptococci to CPT or CAZ alone or in combination with avibactam, whereas Streptococcus pneumoniae and β-hemolytic Streptococcus showed almost 100% susceptibility to both CPT and CPA. Conclusion: The addition of 4 mg/L avibactam greatly increased the activities of CPT and CAZ against most Enterobacteriaceae and P. aeruginosa isolates, whereas no significant changes were observed in Acinetobacter spp. or any of the gram-positive strains.